INVESTIGATION ON THE SPECIFIC ABSORPTION RATE (SAR) IN A 3D HUMAN HEAD MODEL EXPOSED TO ELECTROMAGNETIC RADIATIONS - AHMED, FAYYADH H.; FIEBICH, MARTIN (Journal of Duhok University, 2020)
Exposure human tissue to electromagnetic radiation (EM) from radio wireless frequencies causes many negative health effects. The assessment of the absorbed EM by human tissue depends on the Specific Absorption Rate (SAR) factor. In this paper, a square patch antenna (SPA) is designed to be a source of EM radiation, and optimized to operate at several applicable frequencies, such as GSM 1800, IEEE 802.11 WLAN standard 2.4 GHz and 5.3 GHz bands, and 3.2 GHz WiMAX band. The radiated EM by the SPA antenna is evaluated in a 3D human head model or Specific Anthropomorphic Model (SAM), which consists of two layers, the outer shell (1.5 mm thickness) and filled with tissue simulating liquid (TSL). The investigation involved four aspects, first the distance between the SAM and the EM source has been moved between 0 mm to 50 mm, second for the specific distances (0 mm, 15 mm, 30 mm, and 45 mm) the frequency of EM source has been changed among 1.8 GHz, 2.4 GHz, 3.2 GHz, and 5.3 GHz. Third, the tilt angle (θ) between the SAM and the antenna has been shifted from 00to 900. Finally, the antenna encasement (2 mm thickness plastic material) was removed and the procedure in the first step is repeated to investigate the effect of encasement on the SAR reducing. The results reveal that there is an inversely proportional relation between SAR and distance, SAR and tilt angle. Besides, the antenna encasement has a large impact on attenuating SAR value, while the SAR is directly proportional to frequency. All SAR evaluations were performed by CST-2014 Microwave studio simulator which is built on the Finite-Difference-Time-Domain (FDTD) principle. All calculations are achieved over 1 g and 10 g of mass tissue averaging and according to IEEE/IEC 62704-1 standards.